Social media and libraries in scientific production in United States - França, Maira Nani [UNESP]; Grossi, Angela Maria [UNESP]; Pacios, Ana R. (Universidade Estadual de Campinas, 2021)
Introduction: As organizations responsible for providing accurate and up-to-date information, libraries are continually experimenting with new technological resources and remodeling their services to meet the expectations of their users. At the beginning of the 21st century, social media emerged as yet another opportunity for users to connect to libraries and access their information resources. Objective: This study seeks to identify the characteristics of research on social media and libraries in American scientific production in order to follow its evolution and point out trends. Methodology: This is a descriptive study, of a qualitative and quantitative nature, based on domain analysis, proposed by Hjørland. The research corpus consists of 69 articles published in scientific journals of Information Science in the United States. It was found that interdomain has been discussed by the scientific community since 2006, mainly within the scope of university libraries. We identified a possible epistemic community in formation. The Library 2.0 concept is one of the theoretical contributions that influenced librarians and impacted library services. The knowledge produced on the analyzed interdomain circulates between Information Science and various fields of knowledge, such as Social Communication, Education, Computer Science, Sociology, among others. In addition to Web 2.0, social networks is the term most used by the discursive community, even though social media stands out as a trend. There is a predisposition for research on practical applications, followed by theoretical studies. Emerging terms were identified, which represent the analyzed domain, not yet covered in the main thesaurus used by researchers in the area.
Mídias sociais e bibliotecas na produção científica dos Estados Unidosi
Keywords: Domain analysis; Libraries; Social media; Social networks; Web 2.0 Technologies